[PP.10.23] EVALUATION OF SODIUM INTAKE IN PATIENTS WITH RESISTANT HYPERTENSION: CLINICAL PRACTICE IN GREECE. (September 2016) - Boutari, C.; Stavropoulos, K.; Imprialos, K.P.; Kokkinos, P.; Pittaras, A.; Faselis, C.; Petidis, K.; Deligkaris, P.; Stavropoulos, N.; Athyros, V.; Karagiannis, A.; Doumas, M.
Abstract : Objective: Sodium and water retention is common in patients with resistant hypertension and sodium restriction has been found very effective in such patients. Measurement of sodium excretion in 24-hour (24 h) urine is a reliable marker of sodium intake. The present study evaluated the implementation of the measurement of 24-hour urine sodium in patients with resistant hypertension in the daily practice. Design and method: 186 patients with resistant hypertension were evaluated in our department's hypertension outpatient clinic. Patients were questioned if they: (a) have received advice for sodium intake restriction from their physicians, (b) have restricted sodium intake, (c) consumed small, moderate or large amounts of sodium and (d) have performed a 24 h urine sodium excretion measurement. Results: 169 out of the 186 patients (91%) were instructed to restrict daily sodium intake but the duration of the given instruction was less than one minute in the majority of the cases (86%). 141 of them (76%) stated that they restricted sodium consumption. As for the amount of the intake, 69 (37%) stated that were receiving small amounts, 58 (31%) moderate amounts, 43 (23%) large amounts and the rest 16 (9%) very large amounts of sodium. 24 h urinary collection measurements were performed in 13 patients alone (7%), however only for urine albumin excretion calculations, while only in 2 (1%) of them, sodium excretion was calculated. Conclusions: 24 h urine sodium excretion assessment is performed in a very small portion of patients with resistant hypertension in the daily clinical practice. Physicians should be efficiently informed for this easy, low cost and reliable method of sodium intake specification.